2003
DOI: 10.1074/jbc.m307004200
|View full text |Cite
|
Sign up to set email alerts
|

Pdx1 Expression in Irs2-deficient Mouse β-Cells Is Regulated in a Strain-dependent Manner

Abstract: We previously demonstrated that Irs2 ؊/؊ mice develop diabetes due to ␤-cell growth failure and insulin resistance; however, glucose-induced insulin secretion was increased in islets isolated from Irs2 ؊/؊ mice. Pdx-1, a transcription factor important for maintenance of the ␤-cell function, was recently reported to be severely reduced in Irs2 ؊/؊ murine ␤-cells. We report herein that Pdx-1 expression, including the amount of Pdx-1 localized in the nucleus, is not down-regulated in our Irs2 ؊/؊ murine ␤-cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 54 publications
0
28
2
Order By: Relevance
“…However, we found normal expression of Pdx1 in islets and our findings do not support this conclusion. Indeed others have also reported that Pdx1 expression is normal in Irs2-null beta cells and that differences in expression may be mouse strain dependent [31]. In contrast, we found reduced Slc2a2 expression with concomitant reduction in protein production in PIrs2KO islets and this may further impair beta cell function.…”
Section: Discussioncontrasting
confidence: 55%
“…However, we found normal expression of Pdx1 in islets and our findings do not support this conclusion. Indeed others have also reported that Pdx1 expression is normal in Irs2-null beta cells and that differences in expression may be mouse strain dependent [31]. In contrast, we found reduced Slc2a2 expression with concomitant reduction in protein production in PIrs2KO islets and this may further impair beta cell function.…”
Section: Discussioncontrasting
confidence: 55%
“…4b). In regard to this point, Suzuki et al reported finding that Pdx1 expression in Irs2 −/− mice is regulated in a straindependent manner [29]. Pdx1 expression was not downregulated in our Irs2 −/− murine beta cells that had a C57BL/6J background [29].…”
Section: P22 Phox Expression (Au)mentioning
confidence: 95%
“…Since Kushner et al reported that transgenic overexpression of Pdx1 restored beta cell mass in Irs2 −/− mice [28], Pdx1 may play a role in regulating beta cell mass. Nevertheless, because a haploinsufficiency of Pdx1 led to impaired beta cell function, but not to decreased beta cell mass [30], and because beta cell mass was smaller in our Irs2 −/− mice than in wild-type mice despite the Pdx1 expression level being maintained [29], two different pathways are involved in the stimulation of beta cell function and proliferation by a GKA.…”
Section: P22 Phox Expression (Au)mentioning
confidence: 99%
“…The primers and probes were: DGAT1 forward, TCCGCCTCTGGGCATTC; DGAT1 reverse, GAATCGGCCCACAATCCA; DGAT1 probe, CCATGATGGCT-CAGGTCCCACTGG; DGAT2 forward, GCTGAGTCCCTGAGCTCCAT; DGAT2 reverse, CACAAAGCCTTTGCGGTTCT; DGAT2 probe, CCTG-GCAAGAACGCAGTCACCCTG. The sequences of the cyclophilin primers and probe are described elsewhere (22).…”
Section: Irs2mentioning
confidence: 99%